Автоматична годівниця для котів на базі платформи Arduino uno - Головченко, О. С. (ХНУРЕ, 2023)
An automatic feeder is a device that gives a certain amount of pet food to an animal at a given time. Feeders for cats are designed specifically for this type of pets and may have design features that don’t allow them to be used for feeding other animals. Typically, automatic feeders are used if it is necessary to strictly control the amount of pet food consumed by the pets, or if the owner cannot feed the animal himself for some reason. The automatic feeder ensures that the pet will be received the necessary portion of pet food at the time programmed by the owner